ECOTOURISM-BASED SETTLEMENT PLANNING IN KARANGDALEM I SETTLEMENT, BONGKASA PERTIWI -BALI - Raka Gunawarman; Ni Luh Anik Puspa Ningsih; Made Suryanatha Prabawa (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2019)
The group of Silver Craftsman Cipta Karya Pertiwi Br. Karang Dalem I of the Bongkasa Pertiwi Village, Abiansemal-Badung has the potential to be developed as a tourist destination. This potential is still not able to be processed properly considering the declining silver crafters that do exist in Br. Karang Dalem I. A fundamental problem that needs special attention is that the traditional silver crafters will not become extinct because they are defeated by silver artisans with machines in other areas. The residential environment owned by Br. Karang Dalem I has also become an asset that has a high sale value with a unique atmosphere of a traditional Balinese residential environment. It just needs a little touch so that the face of this region is increasingly supportive as a tourist destination with productive economic products. Lack of understanding and awareness of partner groups about products, management, and the environment are fundamental issues raised in this PKM. The solutions offered are divided into 3 parts: solutions for products, management and environmental management. The output of the solution in the aspect of product production is a change in the mechanism of the production process without reducing production details and traditions. The output of management solutions is improving business performance and community welfare. The output of settlement settlement structuring solutions is the changing face of a stronger environment into a tourism-worthy environment with architectural and landscape elements.